Association between Tpeak-Tend/QT and major adverse cardiovascular events in patients with Takotsubo syndrome. Issue 7 (2nd November 2021) - Braschi, Annabella; Frasheri, Arian; Lombardo, Renzo M.; Abrignani, Maurizio G.; Lo Presti, Rosalia; Vinci, Daniele; Traina, Marcello
Abstract: Background: Conflicting results have been described in the scientific literature regarding the relationship between electrocardiographic parameters and complications in patients with Takotsubo syndrome (TTS). Aim of the present study was to investigate whether there is an association between markers of ventricular repolarization and major adverse cardiovascular events (MACE) during hospitalisation. Methods: A retrospective chart review was conducted on a sample of patients with diagnosis of TTS, based on the fulfilment of the revised Mayo Clinic criteria. MACE included acute heart failure, cardiogenic shock, sustained ventricular tachycardia, ventricular fibrillation, and death. The following parameters, assessed on the admission electrocardiogram, were analysed: ST-segment elevation, ST-segment depression, T wave inversion, presence of Q waves, QT interval, QT interval corrected for heart rate, QT-dispersion, Tpeak–Tend (Tpe) interval, Tpe dispersion, Tpe/QT ratio, and QTpeak/QT ratio. Results: Patients with MACE, compared to patients without MACE, showed more commonly anterior ST-segment elevation and had significantly higher values of Tpe/QT ratio. Low ejection fraction and Tpe/QT ratio > 0.27 identified a sub-population of patients more likely to have MACE during hospitalisation. Conclusions: Tpe/QT ratio represents a useful electrocardiographic parameter in the acute phase of TTS.